2022
DOI: 10.1021/acsapm.1c01827
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Dual-Dynamic Network Materials through Polymer Architectural Features

Abstract: Dynamic materials are known for their self-healing, adhesive, and shape memory applications. Interpenetrating networks (IPNs) are types of materials that can hold dual-dynamic crosslinkers to show complementary chemical and mechanical properties. There have been a number of research studies exploring the dynamic chemistries involved in IPN materials. Not only the bond type but also the polymer network architecture play an important role in governing IPN material properties. In this study, we show that network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 70 publications
1
22
2
Order By: Relevance
“…However, the introduction of static bonds as cross-links sacrificed a portion of the dynamic properties undoubtedly, and the rearrangement of networks was heavily prevented when the ratio of the irreversible cross-links reached ∼60% . In addition, relying on the interpenetrating polymer networks (IPNs), , Zhang’s group and Lin’s group both developed interpenetrating covalent adaptable networks (IPCANs) or reversibly interlocked polymer networks (RILNs) by mixing two preformed immiscible polymers, which required the complete redissolution of the networks in certain cosolvents. , After evaporating the solvents, the two networks relied on different polymer chains interpenetrated with each other and exhibited improved stability while maintaining the reversibility of dynamic bonds . In addition, Chen and co-workers employed well-defined triblock copolymers to construct CANs where the self-assembled microphase separation improved the stability. , …”
Section: Introductionmentioning
confidence: 99%
“…However, the introduction of static bonds as cross-links sacrificed a portion of the dynamic properties undoubtedly, and the rearrangement of networks was heavily prevented when the ratio of the irreversible cross-links reached ∼60% . In addition, relying on the interpenetrating polymer networks (IPNs), , Zhang’s group and Lin’s group both developed interpenetrating covalent adaptable networks (IPCANs) or reversibly interlocked polymer networks (RILNs) by mixing two preformed immiscible polymers, which required the complete redissolution of the networks in certain cosolvents. , After evaporating the solvents, the two networks relied on different polymer chains interpenetrated with each other and exhibited improved stability while maintaining the reversibility of dynamic bonds . In addition, Chen and co-workers employed well-defined triblock copolymers to construct CANs where the self-assembled microphase separation improved the stability. , …”
Section: Introductionmentioning
confidence: 99%
“…This could be due to energy dissipation through hydrogen bonds, short-lived entanglements, and other noncovalent interactions, which are suppressed in the transiently crosslinked state. This is because higher G ″ values, and consequently higher tan δ, could also result from covalent or noncovalent bond exchange. , As noted above, the poly­(Am 50 -AA 50 -MBAm 1.3 ) material fueled with 3.0 M EDC showed a higher tan δ with G ″ ∼ G ′ (Figure S5). This is consistent with the EDC-fueled behavior observed in sol–gel–sol transitions, where higher pendant carboxylic acid concentrations led to lower tan δ .…”
Section: Resultsmentioning
confidence: 71%
“…With the development of polymer materials and the continuous improvement of living standards, the requirements for matrix material properties are gradually becoming stricter. , Especially, the flame retardancy of materials has become an essential indicator due to frequent fire accidents in recent years . Extensive studies have found that there are the following three aspects that affect the efficiency of flame retardants in polymer materials: the types of flame retardant elements or groups in the molecular structure; particle sizes and dispersion forms in the polymer matrix; and the synergistic effect of different types of flame retardant groups. , In addition, the distributions of flame retardant groups at the molecular scale are also likely to affect the efficiency of flame retardants.…”
Section: Introductionmentioning
confidence: 99%